1997
DOI: 10.7164/antibiotics.50.537
|View full text |Cite
|
Sign up to set email alerts
|

Lymphostin (LK6-A), a Novel Immunosuppressant from Streptomyces sp. KY11783: Taxonomy of the Producing Organism, Fermentation, Isolation and Biological Activities.

Abstract: In the course of screening for inhibitors of the lymphocyte kinase, Lck (p56^fc), aiming at novel immunosuppressants, we isolated a novel alkaloid, lymphostin (LK6-A), from the culture broth of Streptomyces sp. KYI1783. Lymphostin was produced in a fermentation mediumsupplemented with a highly porous polymer resin, which prevented the degradation of this compound in the culture broth. Lymphostin inhibited the kinase activity of Lck with an IC50 value of 0.05jUM, and exhibited potent inhibitory activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…We concluded that in the presence of HP20 cercosporamide was efficiently sequestered by the resin, thereby mitigating its self-toxic effect during the course of the fermentation. Adsorbent resins have been in use for some time to mitigate self-toxicity of metabolites produced by many soil bacteria (Table 1), and this technique is also known to increase stability of products during fermentations [2][3][4][5][6][7][8][9][10][11][12][13], but this approach has rarely been used for fungal fermentations [14][15][16].…”
Section: Pdb + 3% Hp20mentioning
confidence: 99%
See 1 more Smart Citation
“…We concluded that in the presence of HP20 cercosporamide was efficiently sequestered by the resin, thereby mitigating its self-toxic effect during the course of the fermentation. Adsorbent resins have been in use for some time to mitigate self-toxicity of metabolites produced by many soil bacteria (Table 1), and this technique is also known to increase stability of products during fermentations [2][3][4][5][6][7][8][9][10][11][12][13], but this approach has rarely been used for fungal fermentations [14][15][16].…”
Section: Pdb + 3% Hp20mentioning
confidence: 99%
“…Fermentations are generally performed in media containing an adsorbent resin to mitigate the self-toxicity of the product to the producer and to increase stability of the products excreted during fermentation. Many of the soil streptomyces producing highly toxic secondary metabolites have been fermented in media containing various adsorbent resins [2][3][4][5][6][7][8][9][10][11][12][13], but this approach has rarely been applied to improve secondary metabolite production in fungal fermentations [14][15][16]. Adsorbent resins are widely used for solid-phase extraction, isolation and purification of a wide variety of pharmaceutical products [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Resin sequesters product and thus lowers feedback inhibition and improves concentration; resin increases product stability; resin collection is easy and does not require sophisticated instrumentation; elution of metabolites from resin consumes much less organic solvent; resin is reusable and thus is environmentally friendly; and resin reduces the length and scale of exposure to organic solvent. Examples of successful usage of HP-20 resin include 100-fold increase of the titer of a fungal selftoxic metabolite [23], significant titer improvement of metabolites produced by Streptomyces [5,7,15,19], and significant increase of product stability during fermentation [7,9], to list only a few.…”
Section: Identification Of Fermentation Parameters and Medium Componentsmentioning
confidence: 99%
“…KY11783 in our laboratories, as described previously. 9) The peptide substrate (Tyr-Ala-Glu)7 used in the assay of Lck activity was synthesized in our laboratories. Lck was partially puriˆed from bovine thymus according to the method of Cushman et al…”
Section: Methodsmentioning
confidence: 99%
“…1), possessing a pyrrolo [4,3,2-de]quinoline skeleton, which is rare among natural products. 9,10) The IC50 for enzyme inhibition was 0.05 mM. In previous studies, the immunosuppressive activity of lymphostin was assessed using the mixed lymphocyte reaction (MLR), which is a measure of T-cell activation followed by IL-2 dependent T-cell proliferation.…”
Section: -7)mentioning
confidence: 99%